Development of the Guided Inquiry Oriented Book of Biology Experiments for Junior High School Students - Rahmatika, Helsa; Fitri, Rahmadhani; Sumarmin, Ramadhan (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
The purpose of this research to produce a guided inquiry oriented book of biology experiments for junior high school students that valid and practice. This research used Plomp model with preliminary research, development or prototyping, and assessment phases. Data analyzed through descriptive. The instruments used in this study were validation and practicality questionnaires. The product validated by 2 biology lecturers and a science teacher, while for practicality was done by a science teacher and 30 junior high school students at one junior highschool in Padang, Indonesia. Based on the results of the study obtained the validity of 3.40 with very valid, experiment by teachers 3.35 very practical and the practicality by students 3.73 with very practical.